Pemanfaatan Hasil Hutan Bukan Kayu Oleh Masyarakat Di Kelurahan Mangkatip Kabupaten Barito Selatan: Utilized Of Non-Timber Forest Products by The Community in Mangkatip Village Dusun Hilir Sub-District South Barito District - Hastari, Belinda; Yulianti, Reri; Kasim, Hiskia (HUTAN TROPIKA, 2024)
Villagers around the forest in Mangkatip village have utilized NonTimber Forest Products (NTFPs). This study aims to identify the types and forms of utilization of NTFPs by the community in Mangkatip village, Dusun Hilir sub-district, South Barito district, Central Kalimantan. The research method used was a respondents interviews with an analytical approach to the utilization of NTFPs by the community in the forest of Mangkatip Village. The results showed that the most utilization of NTFPs by the community in Mangkatip Village were Rattan, Beje Fish, Bajakah, Rubber and Purun, The form of NTFP utilization by the community is in the consumptive, productive and productive consumptive categories. NTFPs that are utilized are traditionally processed, to their own needs, while the use of industrial production is only Rattan